Examining the Underappreciated Role of S-Acylated Proteins as Critical Regulators of Phagocytosis and Phagosome Maturation in Macrophages - Dixon, Charneal L.; Mekhail, Katrina; Fairn, Gregory D. (Frontiers in Immunology, 2021)
Phagocytosis is a receptor-mediated process used by cells to engulf a wide variety of particulates, including microorganisms and apoptotic cells. Many of the proteins involved in this highly orchestrated process are post-translationally modified with lipids as a means of regulating signal transduction, membrane remodeling, phagosome maturation and other immunomodulatory functions of phagocytes. S-acylation, generally referred to as S-palmitoylation, is the post-translational attachment of fatty acids to a cysteine residue exposed topologically to the cytosol. This modification is reversible due to the intrinsically labile thioester bond between the lipid and sulfur atom of cysteine, and thus lends itself to a variety of regulatory scenarios. Here we present an overview of a growing number of S-acylated proteins known to regulate phagocytosis and phagosome biology.